(untitled) (Bangladesh Medical Journal, 2014)
This cross sectional study was carried out to asses the oral health status among tobacco users in the selected rural population of Gazipur district in 2011. Purposive sampling technique was used to collect data from 349 respondents, aged 18 years and above. Their mean age was 36.39 (SD±13.666) years. Among them, 173 (49.6%) were male and 176 (50.4%) were female. Their educational status shows that, majority (35.8%) was illiterate, 32% were from secondary level and only 6.6% from higher secondary & above level. Majority (51%) of the males were either businessman or agricultural worker, where as most of the females (84%) were house wives. The tobacco smoking habit of the respondents showed that 33.2% were current tobacco smokers and rest (66.8%) were currently non smokers. Among the currently non-smokers, 91% were never smokers and rest (9%) were ever smokers. Among current tobacco smokers, almost all were male (98.3%), and among tobacco chewers (46%) majority was female. Seventy one percent respondents had knowledge about health problems due to tobacco intake. The oral health status among the current tobacco consumers (233) showed that 95% had dental stain, 73% had dental plague, 66% had dental calculus, 59% had dental carries, 27% had soft tissue swelling, 15% had leukoplakia, 4% had erythroplakia and 5% had ulceration in their oral cavity. Among the current tobacco non-consumers (116), oral health status showed that 53% had dental stain, 52% had dental plague, 46% had dental calculus, 36% had dental carries, 12% had soft tissue swelling, 5% had leukoplakia and 5% had ulceration in their oral cavity. The study findings showed that oral health status is better among the respondents who were not tobacco consumers. DOI: http://dx.doi.org/10.3329/bmj.v43i2.21387 Bangladesh Med J. 2014 May; 43 (2): 79-83